OPTIMIZATION OF MANUFACTURING IN MSMEs BUSINESSES OF TARO CHIPS - Mboni, La; Safitri, Wulandari; Wader, Elisabeth J; Pinontoan, Monika; Wahyudien, Mohammad Arief Nur (Industrial Engineering Journal – System, 2023)
MSMEs play an important role in driving the economy, even though they are small scale, these businesses are able to help the wheels of a country's economy. MSMEs are a large and diverse sector, and their contribution to economic growth and job creation is very significant. One of the popular MSME sectors is the snack food industry, including the production of taro chips. The obstacle in running this MSME is that it only looks at previous demand without using a production planning strategy. The non-implementation of production planning strategies is motivated by various factors. In this research, we will discuss the optimal production amount for Keladi Chips MSMEs so that profits can be maximized by using the Linear Programming method. The data required to use the Linear Programming method is collecting data such as product type, product yield data, number of working days data, and sales data. This research produces a monthly production profit of Rp. 7,584,000 of them with a production output of taro chips products of 900 packs in one month.